Chronic appendicitis as a cause of chronic rigth lower quadrant abdominal pain - Ramírez Chacón, Jorge Luis (2013)
Abdominal pain is a frequent problem in the medical and surgical consult. There has been written a big number of causes  of chronic abdominal pain, of which there is an estimate of 10-30% that can be explained by a structural or biochemical problems, and in the cases left (70-90%), even though the advances of diagnostic methods, will not be found an organic cause, and it defines as a functional type of abdominal pain. The chronic appendicitis it is always a topic of discussion, due to is not accepted by everyone  as an independent clinical entity. We made an analysis of 20 clinical cases with pathologic diagnosis of chronic appendicitis, from those cases, we subtracts gender,  age, clinical presentation, evolution (time), diagnostic studies made to the patient and treatment, to realize the casuistic of this pathology as a cause of chronic abdominal pain. The criteria to realize a clinical diagnosis of chronic appendicitis is a history of recurrent adbominal pain, more intense in the right lower quadrant, during a time period of more than two weeks, with or without of symptoms associated to appendiceal disease.  The definitive diagnosis of this pathology can be made only by histopahology analysis of the surgical tissue, which reveals data of chronical inflammation.  The only treatment so far is surgery.